Investigating the micro mechanics of cemented sand using DEM - de Bono, John P.; McDowell, Glenn R.; Wanatowski, Dariusz (Wiley, 2015)
The discrete element method has been used to investigate the micro mechanics of cemented sand. High pressure drained triaxial tests are modelled in 3D using a flexible membrane which allows the correct deformation to develop. Simulations with up to 12 MPa confining pressure are presented, which are compared with laboratory experiments on a sand with a range of cement contents. Cementation is modelled using ‘parallel bonds’, and various parameters and strength distributions are investigated. Varying levels of cementation are successfully modelled, with the correct qualitative behaviour observed, and the separate effects of cementation and confining pressures demonstrated. The triaxial behaviour is found to be highly influenced by the distribution of bond strengths.